Intrinsic Nature of Negative Capacitance in Multidomain Hf0.5Zr0.5O2‐Based Ferroelectric/Dielectric Heterostructures. (5th October 2021) - Hoffmann, Michael; Gui, Mengcheng; Slesazeck, Stefan; Fontanini, Riccardo; Segatto, Mattia; Esseni, David; Mikolajick, Thomas
Abstract: Harnessing ferroelectric negative capacitance in Hf0.5 Zr0.5 O2 ‐based thin films is promising for applications in nanoscale electronic devices with ultralow power dissipation, due to their ultimate scalability and semiconductor process compatibility. However, so far, it has been unclear if negative capacitance is an intrinsic material property of ferroelectric Hf0.5 Zr0.5 O2, or if it is an extrinsic effect caused by specific domain configurations and lateral domain wall motion as seen in perovskite ferroelectrics. Here, symmetric and asymmetric Hf0.5 Zr0.5 O2 /Al2 O3 ‐based ferroelectric/dielectric heterostructures are investigated to understand the relationship among depolarization, interfacial charge, domain formation, and negative capacitance. To achieve this, detailed electrical characterization is combined with structural data, analytical modeling, and numerical simulations. The findings suggest that negative capacitance in these ferroelectric/dielectric heterostructures is an intrinsic property of the Hf0.5 Zr0.5 O2 layer, which has important implications for potential applications. Furthermore, it is experimentally observed that the energy barrier for polarization switching in Hf0.5 Zr0.5 O2 is largely independent of the domain configuration and layer thickness, which confirms recent predictions by first principles calculations. Abstract : Materials with negative capacitance are promising for future energy efficient electronics. HfO2 ‐ and ZrO2 ‐based ferroelectrics are ideal for such applications, but the origin of their negative capacitance has been unclear. Here it is shown that the negative capacitance observed in ferroelectric Hf0.5 Zr0.5 O2 thin films is an intrinsic material property and not related to extrinsic effects of lateral domain wall motion.